The relationship between erythema nodosum and prognosis in systemic sarcoidosis: a retrospective cohort study - Elif Afacan Yıldırım; Perihan Aladaǧ Öztürk; Esra Adıșen; Nurdan Köktürk (Sociedade Brasileira de Dermatologia, 2022)
Abstract Background: Erythema Nodosum (EN) is the most common skin manifestation in sarcoidosis and has often been associated with a good prognosis. Objectives: To compare the clinical characteristics and treatment-related features in patients with sarcoidosis according to whether or not EN was seen as a presenting symptom at the time of diagnosis. Methods: A 20-year single-center retrospective study was performed. The following two groups were identified: one group with EN as one of the presenting symptoms at the time of diagnosis of sarcoidosis (EN group) and a second group without EN as a presenting symptom at diagnosis (non-EN group). The clinical characteristics and treatment modalities were collected from the medical records. Results: A total of 122 patients (31 in the EN group, 91 in the non-EN group) were included. Radiological stages of pulmonary disease were significantly lower in the EN group. Articular involvement was more common in the EN group (p = 0.001), whereas other systemic organ involvements (p = 0.025), especially neurological involvement (p = 0.036), were significantly more common in the non-EN group. In the EN group, a higher percentage of patients were managed without systemic therapy (71.0% vs. 54.9%) and spontaneous remission was more frequent (25.0% vs. 14.1%), however, this wasn't statistically significant. Study limitations: Retrospective design. Conclusions: The lower radiological stage of pulmonary sarcoidosis and lower frequency of systemic organ involvement in patients with EN augment the prognostic value of EN highlighted in the literature. However, this study couldn't confirm that the patients with EN would need less systemic therapy in the course of their disease.